STUDY ON THE EFFECTIVENESS OF BANANA STEM PITH (Musa paradisiaca) AS A NATURAL ANESTHETIC IN THE WET TRANSPORTATION OF WHITE SEABASS (Lates calcarifer) JUVENILE - Said Ali Akbar; Asifah Dinda Pratiwi Pulungan; Cut Dara Dewi; Gunawan Gunawan; Adli Waliul Perdana (Universitas Teuku Umar, 2025)
Live fish transportation can induce physiological stress, characterized by increased blood glucose levels and decreased survival rates. This study aims to evaluate the effectiveness of banana pseudostem extract (Musa paradisiaca) as a natural anesthetic for the wet transport of Asian seabass (Lates calcarifer) fry. Observed parameters include induction time, sedative time, blood glucose levels, fish survival, and water quality. The results showed that treatment P3 exhibited the best balance, with an induction time of 10.5 minutes, sedative time of 7 minutes, blood glucose levels of 140 mg/dL, and a survival rate of 90%. Increased ammonia levels were observed after transport, particularly in P5 (0.034 mg/L), while P3 had a lower NH₃ level (0.010 mg/L), indicating better water conditions. Banana pseudostem extract was proven effective as a natural anesthetic in reducing fish stress during transport, with P3 as the optimal treatment.